Attention Deficit Hyperactivity Disorder in a Patient With Congenital Mirror Movement Disorder and Colpocephaly - Yaroglu Kazanci, Selcen (Iran J Pediatr, 2015)
INTRODUCTION: Congenital mirror movement disorder designates involuntary movements on one side of the body that occur as mirror of the intentional movements on the contralateral side. Colpocephaly is described as persistence of fetal configuration of lateral ventricles. CASE PRESENTATION: A two-month old male infant was brought to the hospital due to bilateral identical movements of the hands. Except for bilateral involuntary synkinetic imitative movements in hands, neurological and physical examination was normal. Cranial MRI showed corpus callosum dysgenesis, hypogenesis and dilation of bilateral lateral ventricular posterior horns (colpocephaly). At the age of 7 years, he was started to use metylphenydate to mitigate attention deficit and hyperactivity disorder. The mirror movements were decreasing in amplitude by years and were not so serious to affect normal life activities. CONCLUSIONS: Mirror movements, diagnosed usually during childhood, may be congenital or secondary to neurological diseases. Although they generally do not affect normal life activities, in some cases severity of mirror movements causes a real debilitating disease. In our case the patient was diagnosed at the age of 2 months and on follow-up no debilitating problems were observed. This is the first case to describe the association of colpocephaly and mirror movements. The exact mechanism of this association is not known. Although it is known that mirror movements may be in relation with some pychiatric pathologies, this is the first report of attention deficit and hyperactivity disorder in conjunction with mirror movements and/or colpocephaly. Managing comorbidities, either physical or psyhchological, will help the patient to live in good health without trying to cope with other pathological diseases.